Characteristics of Cellulose Acetate Composite Membranes (Ca/Cs, Ca/Pva, Ca/Peg) As Cu(Ii) Metal Ion Filtration Membranes - Amalia, Vina; Sudiarti, Tety; Mufidah, Rafa; Yuliarti, Yuliarti; Nisrin, Yusrina; Rohmatulloh, Yusuf (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Industrial development in Indonesia has caused increased pollution, including water pollution by heavy metals, one of which is the metal ion Cu(II). Cellulose acetate composite membranes have been widely used to overcome the problem of Cu(II) metal ion content in water, however, studies on the performance of cellulose acetate membranes with various types of chitosan, polyvinyl alcohol (PVA) and polyethylene glycol (PEG) composites have not been widely reported. This research aims to analyze the characteristics of cellulose acetate composite membranes with chitosan, PEG, and PVA using FTIR and SEM and to determine the performance of these cellulose acetate composite membranes in filtering Cu(II) metal from the resulting rejection values. The membrane was made using the phase inversion method and the composite membrane was made using the dip-coating method. The results of characterization using FTIR showed that there were no new peaks in all cellulose acetate composites, so there were only physical interactions in the composites. SEM analysis shows that the surface of the composite membrane is more irregular and the porosity increases. The performance of the composite membrane in filtering Cu(II) metal is better than the pure cellulose acetate membrane.